A quasi-experimental study comparing the effects of L-PRF and white porous titanium granules on the preservation of the buccal bone following immediate implant placement - MCLAUGHLIN, MARK JOSEPH (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2018)
The aim of this quasi-experimental study was to compare the effects of leucocyte and platelet-rich fibrin (L-PRF) and white porous titanium granules (WPTG) on the preservation of the buccal bone plate following immediate implant placement. It also attempted to identify the possible variables affecting this remodelling. 35 implants were placed in the anterior maxilla immediately following tooth extraction and clinical measurements were made to determine the dimensions of the alveolar ridge and the void between the implant and the buccal bone. The voids were then grafted with either L-PRF or WPTG. These measurements were repeated at 2nd stage surgery following 4 months of submerged healing. Both grafting protocols resulted in clinically acceptable results and a 100% survival rate, at least in the short term. WPTG was superior to L-PRF resulting in greater buccal bone thickness and buccal bone height at 4 months, although the differences were not statistically. Statistical analysis determined the gap width, the buccal bone thickness and the horizontal buccal bone dimension were the main indicators for the ridge width at re-entry. It was also demonstrated that specific socket characteristics were key determinants of the magnitude of alveolar ridge remodelling, in particular gap width and gap depth. In conclusion, the grafting protocols employed in this study can be considered successful following immediate implant placement in the anterior maxilla. However, WPTG appears to be superior to L-PRF in preservation of the buccal bone plate.
APPROVED
Keywords: buccal bone plate; Dental surgery; Implant placement